Hole‐Transporting Materials Incorporating Carbazole into Spiro‐Core for Highly Efficient Perovskite Solar Cells. (13th December 2018) - Zhu, Xiang‐Dong; Ma, Xing‐Juan; Wang, Ya‐Kun; Li, Yun; Gao, Chun‐Hong; Wang, Zhao‐Kui; Jiang, Zuo‐Quan; Liao, Liang‐Sheng
Abstract: Hole‐transporting materials (HTMs) play a significant role in hole transport and extraction for perovskite solar cells (PeSCs). As an important type of HTMs, the spiro‐architecture‐based material is widely used as small organic HTM in PeSCs with good photovoltaic performances. The skeletal modification of spiro‐based HTMs is a critical way of modifying energy level and hole mobility. Thus, many spiro alternatives are developed to optimize the spiro‐type HTMs. Herein, a novel carbazole‐based single‐spiro‐HTM named SCZF‐5 is designed and prepared for efficient PeSCs. In addition, another single‐spiro HTM SAF‐5 with reported 10‐phenyl‐10H‐spiro[acridine‐9, 9′‐fluorene] (SAF) core is also synthesized for comparison. Through varying from SAF core to SCZF core as well as comparing with the classic 9, 9′‐spiro‐bifluorene, it is found that the new HTM SCZF‐5 exhibits more impressive power conversion efficiency (PCE) of 20.10% than SAF‐5 (13.93%) and the commercial HTM spiro‐OMeTAD (19.11%). On the other hand, the SCZF‐5‐based device also has better durability in lifetime testing, indicating the newly designed SCZF by integrating carbazole into the spiro concept has good potential for developing effective HTMs. Abstract : Two novel spiro‐type hole‐transporting materials (HTMs) SCZF‐5 and SAF‐5 are designed based on different spiro‐cores, SZCF and SAF, respectively, and are applied in the perovskite solar cells . An impressive power conversion efficiency of 20.10% is achieved in the SCZF‐5‐based device, which is obviously higher than that of commercial HTM spiro‐OMeTAD (19.11%) and SAF‐5 (13.93%).